Qualitative analysis of symmetric fuzzy stochastic differential equations - Malinowski, Marek (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a special approach to stochastic differential equations is explored. Specifically, the values of the mappings involved are fuzzy sets, rather than the usual single values on the real line. Additionally, the equations under consideration are symmetric, meaning that the terms of drift and diffusion appear on both sides of the equation, which is crucial for the properties of the solutions.
Keywords: fuzzy mathematics; fuzzy stochastic differential equations; fuzzy stochastic process; existence of solution; uniqueness of solution